MODEL PEMBELAJARAN TAHFIDZ DALAM PEMBENTUKAN KARAKTER SISWA MADRASAH TSANAWIYAH - Haris, Ahmad; Aljauhari, Shofwan; Faisal, Faisal (Jurnal Hadratul Madaniyah, 2024)
It is not only the ability to read the Qur'an, but also the capacity to shape the character of the student. It is the learning that makes the student accustomed to reading and practicing the holy verses of the Quran in everyday life. Therefore, this study focuses on the application of Tahfiz learning in student character formation, as well as how the implications of Tahfis learning application are embedded. For that, the research uses a qualitative approach to the type of case study. Data collection techniques use observations, interviews and documentation. The results of this study show the method of application of Tahfiz learning in student character formation, namely the Talaqqi method and the Muraja’ah method. The application of tahfiz learning to student characterization is opening, opening activities, and core activities with the provision of hafalan material and depositing hafalan. The resulting implications are in the formation of the student's character into a time discipline, reflecting a reigius attitude as well as responsibility for completing tasks.